2017
DOI: 10.1038/srep44638
|View full text |Cite
|
Sign up to set email alerts
|

TIR/BB-loop mimetic AS-1 attenuates cardiac ischemia/reperfusion injury via a caveolae and caveolin-3-dependent mechanism

Abstract: AS-1, the TIR/BB loop mimetic, plays a protective role in cardiac ischemia/reperfusion (I/R) but the molecular mechanism remains unclear. The muscle specific caveolin3 (Cav-3) and the caveolae have been found to be critical for cardioprotection. This study aimed to evaluate our hypothesis that caveolae and Cav-3 are essential for AS-1-induced cardioprotection against myocardial I/R injury. To address these issues, we analyzed the involvement of Cav-3 in AS-1 mediated cardioprotection both in vivo and in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Whole-cell protein lysates were generated using total lysis buffer; nuclear and cytoplasmic protein lysates were generated using buffer A and buffer C as previously described ( 23 ). Both protein isolation reagents were supplemented with complete protease inhibitor cocktail (Roche Diagnostics, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Whole-cell protein lysates were generated using total lysis buffer; nuclear and cytoplasmic protein lysates were generated using buffer A and buffer C as previously described ( 23 ). Both protein isolation reagents were supplemented with complete protease inhibitor cocktail (Roche Diagnostics, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies suggested that hydrocinnamoyl-L-valyl pyrrolidine (AS-1), a synthetic mimetic of TIR/BB-loop, has protective effects against cardiovascular diseases 1719 . Our previous studies reported that the application of AS-1 prevented the transverse aortic constriction (TAC)-induced hypertrophy in vivo through blocking the activity of transcription factor NF-κΒ and MAPK activation 18 .…”
Section: Introductionmentioning
confidence: 99%